Clinical tests for differentiating between patients with and without patellofemoral pain syndrome - Konstantinos Papadopoulos, MSc; Jane Noyes, PhD; Jeremy G. Jones, MD; Jeanette M. Thom, PhD; Dimitris Stasinopoulos, PhD (World Scientific Publishing, 2014)
Patellofemoral pain syndrome (PFPS) is a very common knee condition with various aetiologies. Because of the nebulous factors of the syndrome, physiotherapists often find it difficult to assess and treat these patients. The aim of this study was to identify the clinical assessment tool that can differentiate PFPS patients from patients with other lower limb conditions. Fifty-two patients from the National Health System (26 with PFPS and 26 with other lower limb conditions) took part in this study. They underwent a series of strength, flexibility, and stress tests. Their pain levels were also recorded. The results showed that among the various clinical tests, only the hip flexion component of the Thomas test was able to differentiate between the two groups. In addition, the stress test showed that the PFPS group could not recover their gluteal muscle strength in the same way the group with the other lower limb conditions did. The Lower Extremity Functional Scale was found to be more able to differentiate between the two groups than the Anterior Knee Pain Scale. This study has shown that it is difficult to find specific clinical tests to diagnose PFPS. More research is needed in this important area.